The Effect Of Static Stretching Exercises On The Flexibility Of Children With Mental Reterdation - Baqiyudin, Galang; Nurhasan, Nurhasan; Suroto, Suroto (International Journal of Educational Research & Social Sciences, 2023)
This research was conducted on moderate category mentally retarded children. This research aims to improve flexibility and balance in children with special needs, namely mentally retarded children. The mentally retarded children who were the research subjects were children aged 5-6 years. This research used a quasi-experimental method, where children were given static stretching treatment and then carried out flexibility and balance tests. The results of this research show that static stretching can have a significant impact on flexibility and balance in mentally retarded children. It can be concluded that static stretching can increase flexibility and balance.